(untitled) (Journal of the College of Education for Women, 2019)
The prophet was against the monopoly . He warned the monopolies with great punishment . inspite of the high price in his time, he did not price , so did the rightely guided caliphes and the ummayads . Umar b abid al-aziz had been asked to price but he refused and said ―the prophet said ― ― God grieves ,pleases and fixes price ―The monopoly was declard announce in the third and the fourth centuries of A.H . because of the weakness of the Islamis State and it’s failure to find the real reasons of it’s existence. Besides that they used the guaranty system in collecting the money . The guaranted shared in monopoly the food-stuff and sold it in high price .Add to that the foreign control on the executive power ,not to be mention the fact that the immigration from the rural areas to the town . And the Abbasid cessation from paying the Arziq to the fighting forces.